Role Ambiguity, Role Conflict Dan Role Overload Sebagai Prediktor Cyberloafing Behavior - Sih Darmi Astuti; Tito Aditya Perdana; Almira Santi Samasta; Rauly Sijabat (STEKOM PRESS, 2023)
Cyberloafing behavior is a form of withdrawal deviance in the workplace which is increasingly surfacing along with technological developments. Cyberloafing behavior not only has a positive impact but also has a negative impact on the company. To maximize the positive impact and minimize the negative impact, this research has an urgency to examine predictors that can explain the occurrence of cyberloafing behavior. The study was conducted using employees from various companies in various industries as research samples. The results of this study indicate that cyberloafing behavior is explained by role ambiguity, role conflict and role overload.